The effect of the use of building materials in the formation of architectural identity Sulaymaniyah city as a case study - Hassan, Niaz H. (Sulaimani Journal for Engineering Sciences, 2019)
Many modern cities are characterized by their own architectural identity through the use of locally available building materials, such as the use of stone in the city of Amman, the brick walls in Baghdad or Halan in Mosul and other modern cities. The research's problem is the lack of interest in the current buildings to use locally available materials to form its architectural identity, especially that these materials (such as Malkandi Stone ) was a unique architectural advantage through its use in buildings of the sixties, seventies and eighties in the city of Sulaymaniyah in addition to its common use in the old heritage buildings . The research focuses on the effect of using locally available building materials in highlighting or playing down the architectural identity. The aim of the research is to identify the obstacles and difficulties that led to the lack of interest in this heritage to be used to highlight the architectural identity of the city of Sulaymaniyah, by the hypothesis that the absence of architectural and planning laws regarding the use of local materials, is a major factor in the absence of architectural identity.
Keywords: Building Materials; Malkandi Stone; Architectural Identity; Sulaymaniyah city